Habitation and Identity. Home Dispositive in Governmentality Policy - Lewartowska-Zychowicz, Małgorzata; Strumska-Cylwik, Longina (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The issue of the text concerns the constitution of human identity in the context of space. The theoretical base of our disquisition is M. Eliade's concept of inhabited space, and M. Heidegger's concept of being-in-the-world. The former points to the social establishment of a framework for individual identity, while the latter refers to the effort of a man to create space thanks to his connections to the things at hand. In its context, the disruption of the direct relation with a man and a thing causes the risk of blocking the development of human identity. The contemporary culture has created practices of governing the private space of people's homes, which is considered to be a part of the capitalist policy of governmentality.